ADSORPSI DAN DESORPSI ION KROMIUM (VI) PADA HDTMA-BENTONIT - Eti Rohaeti (Purifikasi, 2011)
Bentonite is naturally negatively charged, and therefore has a high adsorption capacity towards cations such as mirrored by the cation exchange capacity (CEC) is high. This study aims to bentonite also has a high adsorption ability of anions of chromium (VI), as Cr2O72-, through activation by using hexadecyltrimethylammonium cation (HDTMA +). Bentonite origin Leuwiliang-Bogor, reacted with HDTMA + with an equivalent number of 25%, 50% and 100% CEC bentonite. HDTMA-bentonite produced and tested its ability to adsorps and desorps Cr (VI) anion. Optimum conditions of adsorption of Cr (VI) by HDTMA-bentonite carried out at pH, contact time and concentration of Cr (VI) are different. The analysis showed that the bentonite CEC Leuwiliang me/100g decreased from 54.3 to about 20.7 to 45.1 g me/100 after activated by HDTMA +. The acidity of bentonite also decreased from 4.95 me / g in natural bentonite to about 0.60 to 3.62 me / g after activated. Optimum conditions of adsorption of Cr (VI) by bentonite and HDTMA-bentonite occurs in the pH range of 2 to 5, the contact time of 3 to 4 hours and the concentration of Cr (VI) 200 to 500 ppm. Activation of bentonite with HDTMA + increases the adsorption capacity of bentonite to Cr (VI) of 4.44 mg / g to 11.96 to 22.09 mg / g. Desorption of Cr (VI) of HDTMA-bentonite by distilled water, 0.1 N HCl and 1 M CaCl 2 was relatively small, ranging from 0.89-4.15%, which indicates that Cr (VI) strongly bound in the HDTMA-bentonite.